Analysis of the Behavior of Primary School Students with CES during Physical Education Lessons - I.L. Constantin; M. Chirazi (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
In Romania from 2021, any child, regardless of health status, has the right to enroll in any school unit in the area where they are located. We make it clear that until now these children attended special schools. The study highlights, through the intentional recording of behavior, the manifestations of students with CES during physical education classes that were the basis for the formulation of action recommendations. The analysis finds its usefulness by informing future physical education teachers about situations for which they were not prepared.